A model of cefoperazone tissue penetration: diffusion coefficient and protein binding. - Meulemans, A (1992)
The apparent diffusion coefficient of a bound drug, cefoperazone, was studied. The protein binding of cefoperazone was studied by voltammetry, a technique which permitted instant measurements. The apparent diffusion coefficients were similar in agar and fibrin and lower in rat brain tissue. The influence of protein on the value of the apparent diffusion coefficient was negligible. The hypothesis that only the free drug diffuses was supported. The percentage of binding determined by voltammetry corresponded to the true concentration of drug which diffuses and is much lower than the percentage of binding determined by the ultrafiltration centrifugation method. This discrepancy could be explained by the rate of dissociation of the protein-drug complex.